Cardiorespiratory fitness profile of volunteer firefighters during intermittent incremental exercise: A cross-sectional study - Denisse Bustos; Filipa Cardoso; Manoel J. Rios; Ricardo Cardoso; Diogo D. Carvalho; Joana Guedes; José Torres Costa; Mário Vaz; J. Santos Baptista; Ricardo J. Fernandes (PLoS ONE, 2026)
Purpose We aimed to assess the physiological profile of male volunteer firefighters at a broad spectrum of exercise intensities to determine whether their cardiorespiratory fitness level is adequate to meet the physiological demands of their occupational activities. Methods Thirty-one male volunteer firefighters performed an intermittent incremental treadmill running exercise (with 4 min steps, 1 km·h −1 increments and 30 s rest periods). Cardiorespiratory variables were continuously monitored and blood lactate concentrations were obtained at baseline, throughout rest periods and post-exercise. The study followed a cross-sectional laboratory-based assessment, in accordance with the STROBE guidelines for cross-sectional studies. Results The increase in running velocity resulted in progressively higher values from low to severe exercise intensities in oxygen uptake (from 23.6 ± 7.5 to 44.1 ± 7.6 mL·kg −1 ·min −1 ; p < 0.001; η p 2 = 0.560), heart rate (from 133 ± 24 to 185 ± 14 bpm; p < 0.001; η p 2 = 0.459) and energy expenditure (from 127 ± 50 to 303 ± 51 kJ; p < 0.001; η p 2 = 0.654). Aerobic energy contributions progressively declined (94–83%), while anaerobic contributions increased (6–17%) across the incremental intensity domains. Inverse associations were reported between heart rate and body mass index at heavy (r = −0.38; p = 0.017) and severe (r = −0.34; p = 0.028) intensities, and with fat mass at heavy intensity (r = −0.32; p = 0.037). Conclusions Findings evidenced a moderate to strong effect of exercise intensities on most assessed variables, and approximately half of the participants (~52%) did not meet the age-specific oxygen uptake threshold recommended by widely referenced National Fire Protection Association (NFPA-USA) guidelines for performing their professional duties. Given the firefighters’ high physiological demands, they should follow structured training interventions and receive targeted nutritional guidance to improve their cardiorespiratory fitness while ensuring optimal performance in the field.